New telagogic learning in Post-Covid-19 universities: Learning beyond neo-coloniality and neo-cyber-coloniality - Pitso, T. (South African Journal of Higher Education, 2026)
In Kongo around 1706, Christian Catholic missionaries incinerated Kimpa Vita and her boy child for resisting to buy into their myths and manufactured realities packaged as Christianity, a mind-altering indoctrination of western belief. This was the onset of coloniality using menticide and mendaciloquence projects intended to capture the African mindsets in order to create conditions for colonialism and its looting of African resources. Through Desktop research, a historical perspective and netnography, the study sought to achieve two objectives. 1. To demystify ancient history and make transparent how African mindsets remain captured to this day as colonial looting continues unabated. I also show how neo-coloniality has been repackaged as neo-cyber-coloniality, this idea that advanced technologies in the 21st century thrive on racialised patterning of the internet thus perpetuate racism, prejudice and domination-prone society. 2. To introduce an empowering model and telagogy, a web-based, technology-driven learning. Results show the negative impact of coloniality on the ruptured psyche of Africans and how these 15th century Christianity and 19th century western scientific plinth have captured African mindsets and how the captured African psyche obfuscates the uncovering of unfettered looting of African resources. They also show how the new world order is necessary for telagogy to thrive and sustain a domination-free and just society.